Pengaruh Kurs Dollar, Harga, dan Inflasi Terhadap Volume Ekspor Kepiting Indonesia - Kartika Dewi, Made Dian; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 7, Juli 2015 (pp.746 - 872), 2015)
Indonesian crab prices and high consumption of crab world provide export opportunities. This study aimed at analyzing the effect of simultaneous and partial exchange rate, price of export crab,and  inflation of the export volume of Indonesian crab in 1989-2013. This study was using secondary data, in 1989-2013 and tested multiplier linier regression analysis technique.The result of simultaneous test showed exchange rate, price, and inflation have a significant effect. Partially exchange rate and price is positive significant effect, inflation is negative significant effecton the export volume of Indonesian crab in 1989-2013.The dominant variabel is price of export crab. The government is advised to increase export prevent to deficit.
Keywords: crab export, excange rate, price, inflation